A case-based decision support system for product development. (21st November 2008) - Lau, H.C.W.; Tse, Y.K.; Ho, G.T.S.; Ning, A.
Companies that are developing new products are now facing increasing global competition. Continual success in the marketplace depends upon how efficiently and effectively a company is able to respond to customers' ever changing needs. In this article, a Case-based Product-development Enhancement System (CPES) is designed to help manufacturing industry to support product development by retrieving and analysing useful knowledge and solutions in a timely and cost-effective manner. CPES provides important support for, and information on product development, and enhances effectiveness in product development strategies by integrating techniques such as data warehouse, Online Analytical Processing and Case-Based Reasoning. When applying CPES in a light emitting diode manufacturer, it was possible to maximise resource utilisation, increase work efficiency and greatly reduce cost in product development.